Person-centered aural rehabilitation program improved mood, cognition, and auditory processing in a professional musician who uses a hearing aid and cochlear implant: Case Report - Brennan, Christine; Spence-Olson, McKenna; Cormier, Kayla; Tennant, Sherri; Sharma, Anu (Frontiers in Rehabilitation Sciences, 2024)
IntroductionAural rehabilitation focused on music for individuals with cochlear implants (CIs) and/or hearing aids (HAs) typically emphasizes perceptual skills rather than enjoyment of music. Yet, those with CIs and/or HAs often struggle to enjoy music, complaining that it sounds distorted with the implant or HAs. Typically, aural rehabilitation programs require a significant time commitment, but this may not be feasible or preferable for many patients. This study aimed to evaluate the efficacy of two individualized intensive 3-week home practice programs focused on enjoyment of music, a personal goal for this subject.MethodsThe subject was a professional musician who used a CI and HA. Cognitive measures of global cognitive function, executive function, processing speed, auditory working memory, visual-spatial abilities, verbal fluency, and auditory-verbal memory, as well as auditory electrophysiology (EEG) measures were conducted pre-post experiment 2. Two experiments were undertaken to evaluate responses to two practice programs that incorporated different variations in listening dosage and intervention activities.ResultsExperiment 1 resulted in minimal measurable improvements related to music likability ratings, with the highest dosage condition showing a small increase in average likability rating from baseline to week 3. The results of experiment 2 revealed an improvement in likability ratings only when dosage steadily increased each week. The subject also reported improved mood and decreased frustration during weeks two and three of experiment 2. Finally, we found improvement pre-post experiment 2 on several cognitive and EEG measures.DiscussionThe results of these experiments are encouraging and support the use of an individualized, person-centered, and semi-structured home practice program to increase music enjoyment and improve quality of life and auditory processing for individuals with hearing loss. Future studies should aim to increase sample size and explore pairing person-centered home practice programs with concurrent clinician-lead aural rehabilitation.